GLOBAL PRACTICE OF STATE-SUPPORTING THE AGRICULTURAL PART OF THE NATIONAL ECONOMY AND ITS APPLICATION TO UZBEKISTAN - Sayyora Khalmirzayeva (Scholar Express Journals, 2023)
The article examines in detail the world experience of state support for the agro-industrial complex, assesses the possibilities of its application in Uzbekistan in modern economic conditions. The subject of the research is the state agrarian policy of economically developed countries. The object of the study is the international practice of implementing programs and measures of state support for the agro-industrial complex. Particular attention is paid to the most effective tools and mechanisms of state support for agriculture in various countries of the world.
Keywords: Economics; Agriculture; Agribusiness; Agro-industrial complex